NITRAT CONTENT, PHOSPHATE, SILICATE AND ABUNDANCE OF PLANKTONIK DIATOM IN THE RUPAT OF BENGKALIS REGENCY OF RIAU PROVINCE - Areza Maulana; Irvina Nurrachmi; Sofyan H. Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted in January 2018 in Rupat Water of Bengkalis Regency of Riau Province.The purpose of this research is to know the relationship between nitrate, phosphate and silicates with abundance of diatom in Rupat waters of North and South in Rupat waters. The research method is purposive sampling method with 2 area and divided into 8 point station.The results showed that the concentration of Nitrate, Phosphate and Silicate that is; 0,154 mg/L ; 2,342 mg/L; 0,023 mg/L. Diatom species were found 15 species that is; Asterionella sp, Bacillaria sp, Biddulphia sp, Cerataulina sp, Chaetoceros sp, Ditylum sp, Eucampia sp, Fragilariopsis sp, Guinardia sp, Microspora sp, Minidiscus chilensis, Navicula sp, Rhabdonema sp, Thalassionema sp, Thalassiosira sp. Abundance of diatoms in region 1 and region 2 of 452,159 Ind/L; 503.181 Ind/L.The result of regression test showed that the relationship of nitrate concentration with diatom abundance has a moderate correlation, so that in Rupat waters, the concentration of nitrate, phosphate and silicate belong to oligotrophic waters (less fertile). Key Words : Nitrate, Phospate, Silicate, Abundance Diatoms